(untitled) (University Heart Journal, 2016)
Background: Nearly 40% of patients presenting with Non ST-Segment Elevation Myocardial Infarction (NSTEMI) have Chronic Kidney Disease (CKD). CKD is a powerful predictor of adverse events among NSTEMI patients. CKD is associated with a high prevalence of obstructive coronary artery disease. Objectives: The purpose of the present study was to evaluate the severity of coronary artery disease in patients with Chronic Kidney Disease presenting with Non ST-Segment Elevation Myocardial Infarction. Methods: In this prospective observational study a total of 128 patients with NSTEMI were enrolled. They were divided equally in group I (NSTEMI with CKD) and group II (NSTEMI with normal renal function) on the basis of estimated glomerular filtration rate. Patients were considered to have CKD if he/she had documented history of CKD or estimated glomerular filtration rate <60 mL/min/1.73 m². Angiographic severity of CAD was assessed by evaluation of number of involved vessel, site of lesion, % of stenosis, ACC/AHA lesion classification (Type A, B, C) and TIMI flow grade between the groups. Results: Patients with CKD were significantly older, with a greater prevalence of hypertension, diabetes mellitus, lower left ventricular ejection fraction, and lower haemoglobin level compared with those without CKD. CKD was associated with an increased risk of triple vessel and left main disease. Conclusion: CKD strongly predicts severe coronary artery disease profile among NSTEMI patients. University Heart Journal Vol. 11, No. 1, January 2015; 18-25